2007
DOI: 10.1093/bioinformatics/btm341
|View full text |Cite
|
Sign up to set email alerts
|

ChemDB update—full-text search and virtual chemical space

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 12 publications
0
78
0
1
Order By: Relevance
“…ChemDB (Chen et al, 2005(Chen et al, , 2007 Annotated commercially available molecules ;5,000,000 WOMBAT Data base (World of Molecular BioAcTivity) (Ekins et al, 2007;Hristozov et al, 2007) Bioactivity data for compounds reported in medicinal chemistry journals 331,872…”
Section: B Ligand Databases For Computer-aided Drug Designmentioning
confidence: 99%
“…ChemDB (Chen et al, 2005(Chen et al, , 2007 Annotated commercially available molecules ;5,000,000 WOMBAT Data base (World of Molecular BioAcTivity) (Ekins et al, 2007;Hristozov et al, 2007) Bioactivity data for compounds reported in medicinal chemistry journals 331,872…”
Section: B Ligand Databases For Computer-aided Drug Designmentioning
confidence: 99%
“…(2) Assuming that there is additional pruning resulting from the XOR bound, is it worth the additional computation cost? And if so, should the various pruning algorithms be combined, and how?…”
Section: A New Proximity Filter: the Xor Approach And Its Similarity mentioning
confidence: 99%
“…Development of molecular similarity, especially for drug design areas, has been discussed intensively in several publications [24][25][26][27]. ChemDB application, which is an online tool supported with large commercial chemical database, has been commonly used for molecular similarity analysis in drugs design area [28]. Here we have tried this tool in MIP area.…”
Section: Introductionmentioning
confidence: 99%